Proteasomal-dependent endothelial P2Y6 receptor downregulation as an adaptive mechanism limiting monocyte adhesion during intestinal schistosomiasis - Nathalia F. Oliveira; Matheus M. L. V. Monteiro; Leticia D. Crepaldi; Robson Coutinho-Silva; Luiz Eduardo B. Savio; Claudia L. Martins Silva (Purinergic Signalling, 2026)
Schistosomiasis, a complex chronic intravascular parasitic disease caused by Schistosoma mansoni , triggers a multifaceted host immune response and drives endothelial cells toward a sustained proinflammatory phenotype. The dysfunctional endothelial cells are a hallmark event that contributes to intestinal and liver damage mainly due to an increased monocyte adhesion, but the elevated morbidity unveils the lack of knowledge about disease pathogenesis. Purinergic P2Y 6 receptor (P2Y 6 R) expression is induced in some inflammatory models; therefore, we hypothesized that endothelial P2Y 6 R contributes to monocyte adhesion and mesenteric inflammation in S. mansoni -infected mice. Our results show that, unlike control mice, P2Y 6 R stimulation failed to enhance monocyte adhesion to endothelial cells from infected animals. Molecular analyses using RT-qPCR and immunocytochemistry revealed significant downregulation of P2Y 6 R expression in endothelial cells from the infected group at both transcript and protein levels. Importantly, pretreatment with a proteasome inhibitor restored both P2Y 6 R expression and function, implicating proteasomal degradation as a key mechanism underlying receptor loss during infection. Elevated lipid peroxidation in endothelial cells from the infected group further supported a role for reactive oxygen species (ROS)-dependent proteasome activation and receptor degradation. Collectively, these findings suggest that infection selectively modulates P2Y 6 R signaling by promoting proteasome-dependent downregulation of P2Y 6 R in endothelial cells, which could be an adaptive mechanism to reduce mesenteric inflammation and limit host tissue damage and morbidity during chronic infection. Graphical Abstract